PERANCANGAN APLIKASI FISH SEEKER SEBAGAI MEDIA PEMBELAJARAN DI SEKOLAH MENENGAH KEJURUAN - Zulva Azizah, Naila; Putri Bachri, Naisya; Yustia Zahra, Karin; Bintang Arkanaufal, Muhammad (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2025)
The development of digital application-based learning media is becoming increasingly important in supporting the teaching and learning process, especially in Vocational High Schools (SMK) that emphasize practical and contextual competencies. This study aims to design the Fish Seeker application as an interactive learning medium in the field of freshwater fisheries (Agribusiness of Freshwater Fisheries – APAT) at SMK. The development model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). In the Analysis stage, the needs of students and teachers for interesting and relevant learning media were identified. The analysis revealed a demand for media that could display various species of freshwater fish along with their scientific names and provide interactive learning experiences. During the Design stage, core features such as a freshwater fish gallery, digital learning modules, quizzes on fish species and scientific names, and a completion screen after each quiz were developed. The application was built in the Development stage using Java and XML for Android. Implementation involved testing the application with students and a brief training session for teachers. Evaluation was conducted formatively and summatively, showing that the Fish Seeker application enhances student interest and contextual understanding. The application is therefore considered suitable as a digital learning alternative in SMK. Future improvements could include AI integration for automatic fish identification and learning outcome tracking.